Responding to reviewers. (August 2019) - Linton, Jonathan D.
Abstract: At its extremes, the review process is the part of publishing that can lead to either non-publication of research or transformation of good work into a seminal article. While this process has tremendous importance and impact, very little is written about it. Consequently, a brief article is provided to offer advice and guidance in assisting new and experienced researchers in navigating this process. While the article is based on the experience of a management/social science researcher, similar advice has been found helpful to colleagues in other departments and faculties. Consequently, the guidance is worth considering regardless of what academic discipline that you are writing for.